An Analysis of Literary and Cultural Content in the TISOL Textbook ‘Sahabatku Indonesia’ - Chindy, Chindy Yulia Permatasari; Syafryadin, Syafryadin (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
ABSTRACT In TISOL teaching, one of the critical factors in supporting the learning process is the use of learning media such as teaching materials or textbooks. Hence, this research aims to determine whether literary and cultural content elements have been included in the BIPA textbook "Sahabatku Indonesia", especially at levels C1-C2. To obtain the results of this research, a qualitative approach was used with a content analysis method based on the scale developed by Nurgiyantoro. Therefore, the results of this research, in the BIPA book entitled ’My Indonesian Friend’, volume I, is only 65% , and for volume II, the percentage is 72% if included in the Nurgiyantoro scale percentage classification, this is included in the "Quite Suitable" category. The book’s content is considered appropriate to students’ needs in terms of consistency, depth, and breadth of material, as well as accuracy and cultural and literary content displayed. So, these two books can be used by teachers in teaching BIPA through sufficient cultural and literary approaches. As for the development of these two books, the researcher suggests that the relationship between cultural and literary content be readjusted according to the theme of each unit or chapter. Key Words: BIPA, Cultural Content, Literature, Foreign Students